Inverse relationship between vitamin D status and insulin resistance and the risk of impaired fasting glucose in Korean children and adolescents: the Korean National Health and Nutrition Examination Survey (KNHANES) 2009–2010. Issue 4 (19th September 2013) - Chung, Seung Joon; Lee, Young Ah; Hong, Hyunsook; Kang, Min Jae; Kwon, Hyun Jin; Shin, Choong Ho; Yang, Sei Won
Abstract Objective To investigate whether low vitamin D status was related to insulin resistance (IR) or impaired fasting glucose (IFG) in Korean adolescents, after adjusting for total body fat mass (FM). Design A cross-sectional study. Setting Korea National Health and Nutrition Examination Survey (KNAHNES) 2009–2010. Subjects In total, 1466 participants (769 males) aged 10–19 years were assessed for serum 25-hydroxyvitamin D (25(OH)D) levels, for FM by whole-body dual-energy X-ray absorptiometry and for IR by homeostasis model assessment (HOMA-IR) after an 8 h fast. Results Age-, sex-, season- and physical-activity-adjusted regression models showed that serum 25(OH)D levels were significantly related to markers of adiposity (P = 0·016 for FM (g), P = 0·023 for FM (%) and P = 0·035 for fat mass index). When the participants were stratified into three 25(OH)D categories (<37·5 nmol/l (n 553), 37·5 to < 50 nmol/l (n 543) and ≥ 50 nmol/l (n 370)), significantly decreasing trends were observed for fasting insulin (all P < 0·001), HOMA-IR (all P < 0·001) and the odds ratios for IFG (all P for trend < 0·05) from the lowest to the highest 25(OH)D category, after adjustments for age, sex, physical activity and all markers of adiposity. In the multivariate logistic regression analysis, the likelihood of participants in the lowest serum 25(OH)D category having IFG was 2·96–3·15 compared with those in the highest 25(OH)D category (all P < 0·05). Conclusions There was a significant inverse relationship between vitamin D status and IR and the risk of IFG, independent of adiposity, in Korean adolescents.